2008
DOI: 10.1007/s10439-008-9512-1
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Associated Thermographic Changes in Young and Elderly Subjects

Abstract: This study aimed at evaluating the thermographic changes associated with localized exercise in young and elderly subjects. An exercise protocol using 1 kg load was applied during 3 min to the knee flexors of 14 elderly (67 +/- 5 years) and 15 young (23 +/- 2 years) healthy subjects. The posterior thigh's skin temperature of the exercised limb and contralateral limb were measured by infrared thermography on pre-exercise, immediately post-exercise, and during the 10-min period post-exercise. Difference (p < 0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 24 publications
3
69
0
6
Order By: Relevance
“…Studies in the field of thermography have evaluated only the lower limbs [14], hands [8] or whole body [4]. The results of this study suggest different acclimatization times for different body areas.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Studies in the field of thermography have evaluated only the lower limbs [14], hands [8] or whole body [4]. The results of this study suggest different acclimatization times for different body areas.…”
Section: Discussionmentioning
confidence: 82%
“…The scientific use of thermography began in medical research, in which it has been used to diagnose vascular disease [11], inflammation [12], tumors [6,13], metabolic disorders and abnormalities in body temperature [12]. In the field of physical activity and sports, some studies have used the technique to study differences in thermogenesis between young and elderly people [14], the effect of exercise on hand temperature [8], and the distribution and variation of T SK during progressive exercise [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the differences observed in T SKIN from TC were sizeable. Utilising TC in a dynamic, ecologically valid situation is in contrast to the techniques adopted in the majority of previous research with thermal cameras that has shown broadly encouraging results (Merla et al 2010;Ferreira et al 2008;Chudecka & Lubkowska 2012), albeit not unanimously (Fernandes et al 2014). Specifically, tripod mounted cameras have been used to generate thermograms of participants who have spent up to 40 minutes in thermo-neutral conditions.…”
Section: Skin Temperature Validity Comparisonmentioning
confidence: 99%